Al-Zn-BASED ALLOY COATED STEEL SHEET
Patent Information
- Application Number
- JP2023138921
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明によれば、平面部耐食性と端面部耐食性の両方を向上させることが可能なAl-Zn系合金被覆鋼板を提供できる。
Smart Images

Figure 2025033296000006 
Figure 2025033296000007 
Figure 2025033296000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an Al-Zn alloy coated steel sheet. [Background technology]
[0002] As an example of a steel sheet having a coating layer made of a Zn alloy, a hot-dip zinc alloy-plated steel sheet is known. Since the coating layer made of a Zn alloy has excellent durability, the hot-dip zinc alloy-plated steel sheet is used in a wide range of applications such as automobiles, building materials, and home appliances.
[0003] The Zn alloy, which is the coating layer of hot-dip zinc alloy-coated steel sheets, acts as a sacrificial anticorrosive agent against steel, protecting the underlying steel in atmospheric corrosive environments. The metal structure of Zn alloys containing Al is mainly composed of a phase with a high concentration of Al and a phase with a high concentration of Zn, and it is believed that Al improves the dissolution resistance of the coating layer, while Zn exerts a sacrificial anticorrosive effect.
[0004] That is, the corrosion resistance of hot-dip zinc alloy-coated steel sheets is expressed as follows: (1) when the entire surface of the steel substrate is covered with the coating layer (Zn alloy), the dissolution rate of the coating layer is low, and corrosion resistance due to the barrier effect of the coating layer is maintained; and (2) when the coating layer is partially lost and the steel substrate is exposed, the coating layer dissolves preferentially, and the effect of sacrificial corrosion protection of the steel substrate is maintained for a long period of time. The sacrificial corrosion protection effect improves the corrosion resistance of steel, for example, at the cut end surface of the hot-dip zinc alloy-coated steel sheet. Therefore, in order to improve the corrosion resistance of hot-dip zinc alloy-coated steel sheets, it is necessary to control the chemical composition and metal structure of the Zn alloy that constitutes the coating layer so as to achieve a high level of both the dissolution resistance and sacrificial corrosion protection of the coating layer.
[0005] Patent Documents 1 and 2 are examples that focus on controlling the coating structure. Patent Document 1 focuses on thermal spraying as a method other than hot-dip galvanizing, and discloses a steel sheet coated with Zn alloy particles containing Mg. Thermal spraying is a coating method that does not require immersion in molten metal, and has the advantage of having a wide melting point tolerance range for metals or alloys that can be coated. However, there are concerns about reduced adhesion and productivity with particles with a particle size of less than 5 μm.
[0006] Patent Document 2 discloses a method for producing a corrosion-resistant zinc alloy coated steel wire by coating the outer circumference of a steel wire with a mixed powder of Zn and Al and sintering the coated steel wire. However, in Patent Document 2, the metal structure of the alloy coating layer containing Al and Zn is not refined, and the dissolution resistance and sacrificial corrosion protection of the alloy coating layer are insufficient. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2017 / 057638 [Patent Document 2] Japanese Patent Application Publication No. Hei 1-180909 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an Al-Zn-based alloy coated steel sheet capable of improving both the corrosion resistance of the flat surface portion and the corrosion resistance of the edge surface portion. [Means for solving the problem]
[0009] [1] A steel plate and an alloy coating layer containing Zn and Al arranged on the surface of the steel plate, The average chemical composition of the alloy coating layer contains 6 to 80 mass% Al, with the remainder being Zn and impurities, The metal structure of the alloy coating layer is composed of a phase containing 80 atomic % or more of Zn and a phase containing 80 atomic % or more of Al, The Al-Zn based alloy coated steel sheet, wherein the phase containing 80 atomic % or more of Zn has a KAM value of 0.55 to 0.70°, and the phase containing 80 atomic % or more of Al has a KAM value of 1.00 to 4.00°. [2] The half-width of the X-ray diffraction peak of the (203) plane of the phase containing 80 atomic % or more of Zn is in the range of 0.18 to 0.24°, The Al-Zn alloy coated steel sheet according to [1], wherein the half width of the X-ray diffraction peak of the (331) plane of the phase containing 80 atomic % or more of Al is in the range of 0.34 to 0.60°. [3] An Al-Zn based alloy coated steel sheet according to [1] or [2], wherein, when a region surrounded by grain boundaries having an average crystal orientation difference of 15° or more according to EBSD analysis is defined as a crystal grain, the average grain size of the phase containing 80 atomic % or more of Zn is in the range of 0.1 to 4 μm, and the average grain size of the phase containing 80 atomic % or more of Al is in the range of 0.1 to 4 μm. Effect of the Invention
[0010] According to the present invention, it is possible to provide an Al-Zn alloy coated steel sheet capable of improving both the corrosion resistance of flat surfaces and the corrosion resistance of edge surfaces. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic diagram of an alloy coating layer of an Al-Zn-based alloy coated steel sheet according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating a method for evaluating the corrosion resistance of an end face portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present inventors have conducted extensive research to improve the corrosion resistance of an Al-Zn based alloy coated steel sheet having an alloy coating layer containing Al and Zn. In general, a hot-dip coating layer containing 6 to 80 mass% Al with the remainder being Zn and impurities contains a Zn phase mainly composed of Zn and an Al phase mainly composed of Al. The average grain size of the Zn phase and the Al phase is about 5 to 200 μm, depending on the composition. However, the average grain size of both the Zn phase and the Al phase is not simultaneously refined to several μm, and one of the grain sizes of the Zn phase and the Al phase tends to be larger. When observing the metal structure of a conventional hot-dip coating layer, a Zn phase exists between relatively large Al phases, or an Al phase exists between relatively large Zn phases. The corrosion form of a hot-dip coating steel sheet having such a hot-dip coating layer is that first, the Zn constituting the Zn phase dissolves, thereby exerting a sacrificial corrosion protection ability, and then, the part where the Zn has dissolved is filled with an oxidation product of aluminum, thereby exerting a barrier property.
[0013] The present inventors have found that, in a conventional hot-dip plated steel sheet, Zn powder and Al powder are pulverized by a ball mill, and then the pulverized powder is sintered by a spark plasma sintering method, so that a coating layer can be formed on the steel sheet surface in which the Zn phase and Al phase are finely divided and the Al phase is highly strained. In such a coating layer, Al is preferentially dissolved in the early stage of corrosion, so that a passive film of aluminum oxide is formed on the plating layer surface early, and the corrosion resistance of the flat surface is ensured by the barrier function of the passive film, and further, the sacrificial corrosion protection of the Zn phase is maintained for a long period of time. It has been found that this makes it possible to improve both the corrosion resistance of the flat surface and the corrosion resistance of the end surface.
[0014] Hereinafter, an embodiment of the present invention will be described. The Al-Zn alloy coated steel sheet of this embodiment comprises a steel sheet and an alloy coating layer containing Zn and Al arranged on the surface of the steel sheet, the chemical composition of the alloy coating layer containing 6 to 80 mass% Al with the remainder being Zn and impurities, the metal structure of the alloy coating layer comprising a phase containing 80 atomic % or more of Zn and a phase containing 80 atomic % or more of Al, the KAM value of the phase containing 80 atomic % or more of Zn being 0.55 to 0.70°, and the KAM value of the phase containing 80 atomic % or more of Al being 1.00 to 4.00°. In addition, in the Al-Zn based alloy coated steel sheet of this embodiment, it is preferable that the half width in X-ray diffraction measurement of the (203) plane of the phase containing 80 atomic % or more of Zn is in the range of 0.18 to 0.24°, and the half width in X-ray diffraction measurement of the (331) plane of the phase containing 80 atomic % or more of Al is in the range of 0.34 to 0.60°. In addition, in the Al-Zn based alloy coated steel sheet of this embodiment, when a region surrounded by grain boundaries having an average crystal orientation difference of 15° or more according to EBSD analysis is defined as a crystal grain, it is preferable that the average grain size of the phase containing 80 atomic % or more of Zn is in the range of 0.1 to 4 μm, and the average grain size of the phase containing 80 atomic % or more of Al is in the range of 0.1 to 4 μm.
[0015] In the following description, the "%" for the content of each element in the average chemical composition means "mass%." Furthermore, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower and upper limits. When the numerical values before and after "~" are followed by "more than" or "less than or equal to," the numerical range does not include these numerical values as the lower or upper limit.
[0016] The material of the steel plate is not particularly limited. For example, various types of steel can be used, such as general steel, Al-killed steel, extra-low carbon steel, high carbon steel, various high tensile steels, and some high alloy steels (steels containing strengthening elements such as Ni and Cr).
[0017] The alloy coating layer disposed on the surface of the steel sheet may be formed on at least one surface in the sheet thickness direction of the steel sheet, or may be formed on both surfaces in the sheet thickness direction. Also, the alloy coating layer may be formed on an end surface of the steel sheet.
[0018] The amount of the alloy coating layer is, for example, 35 to 85 g / m 2 The coating weight of the alloy coating layer is correlated with corrosion resistance, and the thicker the layer, the better the corrosion resistance. However, applying a thick alloy coating layer requires a large amount of metal, which leads to increased costs. Therefore, the coating weight of the alloy coating layer is set to 85 g / m. 2 It is preferable that the coating weight of the alloy coating layer is 35 g / m or less. 2 If the thickness is less than 35g / m, the corrosion resistance will decrease. 2 That's good.
[0019] Next, the average chemical composition of the alloy coating layer will be described.
[0020] Al: 6~80% by mass Al forms a phase containing 80 atomic % or more of Al (hereinafter referred to as Al-containing phase) in the alloy coating layer. Since Al contained in the Al-containing phase is given high strain by strong working, it dissolves preferentially in the early stage of corrosion, forms a passive film on the surface of the plating layer, enhances the barrier property of the alloy coating layer, and improves the corrosion resistance of the flat surface. In order to obtain such an effect, it is necessary that Al is contained in 6 mass % or more. On the other hand, if the Al content exceeds 80 mass %, the Zn content becomes relatively small, the sacrificial corrosion protection property decreases, and the corrosion resistance of the end surface decreases. Therefore, the Al content is set to 6 to 80 mass %. The Al content may be 10 mass % or more, 20 mass % or more, 30 mass % or more, 40 mass % or more, or 50 mass % or more. The Al content may be 70 mass % or less, 65 mass % or less, or 60 mass % or less.
[0021] Remainder: Zn and impurities Zn constitutes a phase containing 80 atomic % or more of Zn (hereinafter referred to as Zn-containing phase) in the alloy coating layer, and must be contained as the remainder. Zn exerts sacrificial corrosion protection performance during corrosion and improves the corrosion resistance of the end face.
[0022] Impurities refer to components contained in raw materials or components mixed in during the manufacturing process, but not intentionally included. Examples of impurities include oxygen and Fe. The amount of impurities is a maximum of 1% or less, preferably 0.1% or less.
[0023] To identify the average chemical composition of the alloy coating layer, the alloy coating layer is peeled off and dissolved using an acid containing an inhibitor that suppresses corrosion of the steel sheet to obtain an acid solution. The resulting acid solution is then measured using ICP atomic emission spectroscopy or ICP-MS to obtain the chemical composition. There are no particular restrictions on the type of acid, so long as it is an acid that can dissolve the alloy coating layer. If the area and weight are measured before and after peeling, the adhesion amount (g / m2) of the alloy coating layer can be determined. 2 ) can also be obtained at the same time.
[0024] Next, the structure of the alloy coating layer will be described. The alloy coating layer of this embodiment is composed of a Zn-containing phase containing 80 atomic % or more of Zn and an Al-containing phase containing 80 atomic % or more of Al. FIG. 1 shows a schematic diagram of an SEM photograph of a cross section of the alloy coating layer. FIG. 1 is a diagram showing a schematic representation of an Al-containing phase and a Zn-containing phase based on the composition of Al and Zn. As shown in FIG. 1, the alloy coating layer of this embodiment has a form in which a fine Zn-containing phase and an Al-containing phase are mixed. In FIG. 1, the white part is the Zn-containing phase, and the shaded part is the Al-containing phase. Note that the grain size of each phase as understood from the schematic diagram of the SEM photograph in FIG. 1 is different from the grain size of each phase when the region surrounded by grain boundaries having an average crystal orientation difference of 15° or more is defined as a crystal grain by EBSD analysis. In this embodiment, as described later, the grain size as understood by EBSD analysis is adopted as the grain size of the Zn-containing phase and the Al-containing phase.
[0025] The Zn-containing phase may contain Al in addition to 80 atomic % or more of Zn. The amount of Zn in the Zn-containing phase may be 90 atomic % or more, 95 atomic % or more, or 99 atomic % or more. The Al-containing phase may contain Zn in addition to 80 atomic % or more of Al. The amount of Al in the Al-containing phase may be 90 atomic % or more, 95 atomic % or more, or 99 atomic % or more.
[0026] The chemical compositions of the Zn-containing phase and the Al-containing phase are understood by quantitatively analyzing the elements constituting the Zn-containing phase and the Al-containing phase, respectively, using an energy dispersive X-ray spectroscopy (EDS) attached to a transmission electron microscope (TEM). Specifically, a test piece is cut out from an Al-Zn alloy-coated steel plate on which an alloy coating layer is formed, using a cryo-FIB (Focused Ion Beam) method, and the cross-sectional structure of the cut out test piece is observed with a TEM at a magnification that allows multiple pieces of each phase to be included in the observation field. For example, the transmission electron microscope can be JEM-2100F (manufactured by JEOL Ltd.), the EDS measurement device can be JED-2300T (manufactured by JEOL Ltd.), and the FIB device can be NB5000 (manufactured by Hitachi High-Technologies Corporation). The cutting by FIB method is performed at an acceleration voltage of 40 to 5 kV after forming an Au vapor deposition film as an electron irradiation protection film before TEM observation. A Cu mesh is used as the sample holding mesh. To identify the constituent elements of each phase, quantitative analysis of Zn and Al is performed at five or more points in each phase using TEM-EDS. The average values of the Zn and Al concentrations at each point in each phase are adopted as the chemical composition of each phase. Observation and EDS analysis are measured at an acceleration voltage of 200 kV and a probe diameter of 1 nmΦ.
[0027] Next, we will explain the KAM value. The KAM value (Kernel Average Misorientation) is the average value of the misorientation between a pixel of interest and adjacent pixels when the crystal orientation of each crystal grain that makes up a polycrystalline metal structure is analyzed by electron backscattering beam diffraction (ESBD), and is often used as a parameter that indicates local strain, and is generally expressed by the following formula, for example (Source: Journal of the Japan Institute of Metals, Vol. 74, No. 7 (2010) pp. 467-474). The degree of local strain can be grasped by this KAM value. The larger the value, the greater the local strain.
[0028]
number
[0029] In equation (1), α ij is the crystal orientation difference between measurement point i and measurement point j, and n is the number of measurement points.
[0030] The average KAM value of the Zn-containing phase according to this embodiment is in the range of 0.55 to 0.70°, and the average KAM value of the Al-containing phase is in the range of 1.00 to 4.00°. Thus, in this embodiment, the KAM value of the Al-containing phase is larger than that of the Zn-containing phase, and the local strain is high. Since the KAM value of the Al-containing phase is in the range of 1.00 to 4.00°, Al in the Al-containing phase is preferentially dissolved when placed in a corrosive environment. If the KAM value of the Al-containing phase is less than 1.00°, the local strain of the Al-containing phase is low, preferential corrosion of Al does not occur, and early formation of a passive film by aluminum oxide does not occur, so that the corrosion resistance of the flat part may decrease. On the other hand, since the analysis is performed with the maximum value set to 5°, the KAM value does not exceed 5°, and the effect is saturated even if the KAM value is increased, the KAM value of the Al-containing phase is set to 4.00° or less.
[0031] In addition, the KAM value of the Zn-containing phase theoretically cannot fall below 0°, and if it is less than 0.55°, the local strain is small, the dissolution rate of the Zn-containing phase is slow, and the corrosion resistance of the edge surface may decrease. If the KAM value of the Zn-containing phase exceeds 0.70°, the dissolution rate of the Zn-containing phase increases with an increase in local strain, and the wear of the plating accelerates, which may decrease the long-term corrosion resistance of the edge surface.
[0032] Next, the half-width of the X-ray diffraction peak will be described. The larger the half-width of the X-ray diffraction peak, the smaller the crystallite size of the phase tends to be. On the other hand, when a metal is generally subjected to strong processing and strain is introduced, many dislocations are generated in the structure and the crystallite size becomes smaller. Therefore, the half-width of the X-ray diffraction peak can be regarded as a parameter representing the degree of strain. That is, it can be said that the larger the half-width of the X-ray diffraction peak, the larger the strain applied. In this embodiment, the half-width of the X-ray diffraction peak of the (331) plane of the Al-containing phase is preferably in the range of 0.34 to 0.60°. When the half-width of the X-ray diffraction peak of the (331) plane of the Al-containing phase is in the range of 0.34 to 0.60°, the strain in the Al-containing phase is increased, and thus the Al-containing phase is more likely to dissolve preferentially, the passive film is formed early, and the corrosion resistance of the flat surface is improved.
[0033] The half width of the X-ray diffraction peak of the (203) plane of the Zn-containing phase is preferably in the range of 0.18 to 0.24°. When the half width of the X-ray diffraction peak of the (203) plane of the Zn-containing phase is in the range of 0.18 to 0.24°, the dislocation density in the Zn-containing phase becomes relatively low, and thus the sacrificial corrosion protection by the Zn-containing phase is further improved.
[0034] Next, in this embodiment, when a region surrounded by grain boundaries having an average crystal orientation difference of 15° or more by EBSD analysis is defined as a crystal grain, it is preferable that the average grain size of the Zn-containing phase is in the range of 0.1 to 4 μm, and the average grain size of the Al-containing phase is in the range of 0.1 to 4 μm, which can further improve the corrosion resistance of the flat surface portion and the end surface portion of the alloy coating layer.
[0035] The KAM value, half width of the X-ray diffraction peak, and average particle size of the Al-containing phase and the Zn-containing phase can be controlled by the grinding time in a ball mill, as described later.
[0036] The methods for measuring the KAM value, the half width of the X-ray diffraction peak, and the average particle size in this embodiment will be described.
[0037] (KAM value and average particle size) The surface of the alloy coating layer according to this embodiment is polished using #1500 silicon carbide paper, then finished to a mirror surface using a liquid in which diamond powder with a particle size of 1 to 6 μm is dispersed in a lubricating liquid containing alcohol, and then final polishing is performed using colloidal silica in this order. In this manner, a measurement sample is prepared.
[0038] The measurement sample is observed using a scanning electron microscope. The scanning electron microscope is equipped with an EBSD analysis device and an EDS measurement device. For example, the field emission scanning electron microscope can be a scanning electron microscope (FE-SEM: SU-70) manufactured by Hitachi High-Tech Corporation, the EBSD analysis device can be Digi View (manufactured by TSL Solutions), and the EDS measurement device can be Octan elect super (manufactured by Ametech Co., Ltd.).
[0039] The measurement magnification is 5000 times, the measurement area is a 15μm×30μm area of the coating layer cross section, the measurement interval is 0.03μm step, the acceleration voltage is 15kV, the working distance is 15mm, and the secondary electron image is taken with a scanning electron microscope.
[0040] The obtained photographed image is subjected to elemental analysis by EDS to identify the Zn-containing phase and the Al-containing phase. The Zn-containing phase is defined as the region where 80 atomic % or more of Zn is detected, and the Al-containing phase is defined as the region where 80 atomic % or more of Al is detected.
[0041] Next, the same field of view is subjected to EBSD analysis at an analysis speed of 200 to 300 points / second using an EBSD analyzer. The average grain size of the Al-containing phase and the Zn-containing phase is calculated using the software "OIM Analysis (registered trademark)" attached to the EBSD analyzer. With respect to the crystal orientation information obtained by EBSD analysis, the region surrounded by grain boundaries with an average crystal orientation difference of 15° or more is defined as a crystal grain, and the average crystal grain size is calculated. In calculating the average crystal grain size, the measurement target is crystal grains with a grain size of 0.05 μm or more.
[0042] Next, the KAM value is measured under the following conditions using the software "OIM Analysis (registered trademark)".
[0043] Nearest neighbor: 1st (If it is 1st, the azimuth difference is calculated using the nearest pixel.) Perimeter only If there is a difference in direction of 5° or more, all directions are specified as a difference of 5°. ·Maximum orientation difference: within 5°
[0044] (X-ray diffraction peak half-width) As sample pretreatment, the measurement sample used in the EBSD analysis is chemically polished to a depth of approximately 3 μm using a mixture of diluted hydrofluoric acid and nitric acid to remove polishing distortion. Then, X-ray diffraction measurements are performed under the conditions shown in Table 1 to identify the X-ray diffraction peaks of the Zn (203) plane and the Al (331) plane. The diffraction peak position 2θ and half-width WL are obtained by fitting with a Lorentzian function after removing the background and Kα2 radiation. The half-width derived from the instrument is obtained by interpolation using the half-width of the standard sample (LaB6). The true half-width is obtained by subtracting the "half-width derived from the instrument" from the "half-width of the sample".
[0045] [Table 1]
[0046] Next, a method for producing the Al-Zn alloy coated steel sheet of this embodiment will be described. In this embodiment, a mixed powder of Zn powder and Al powder, which is the raw material powder, is pulverized by a planetary ball mill and alloyed by mechanical alloying, and the mixed powder after ball milling is sintered on a steel plate by a spark plasma sintering method to produce the alloy.
[0047] The raw material powders are Zn powder and Al powder. The Zn powder has a purity of, for example, 99.99% or more. The Al powder has a purity of, for example, 99.99% or more. The mixture ratio of the Al powder and the Zn powder is such that Al is contained in an amount of 6 to 80 mass%.
[0048] Regarding the particle size of the raw material powder, for example, the particle size range of the Zn powder is preferably 75 μm or less, and the particle size range of the Al powder is preferably 180 μm or less. This makes it possible to manufacture an alloy coating layer having fine Al-containing phases and Zn-containing phases.
[0049] Generally, the ball mill includes a rotary ball mill, a vibration ball mill, a planetary ball mill, an agitation ball mill, etc. In the present embodiment, any ball mill may be used, but it is preferable to use a planetary ball mill which can perform the grinding process in a shorter time.
[0050] The materials of the mill container and balls used in ball milling are generally alumina, zirconia, stainless steel, tungsten carbide, etc. In this embodiment, the materials of the mill container and balls are not limited, but if it is desired to alloy the raw material powder in a shorter time and produce powder with fewer impurities, it is preferable to use a container and balls made of stainless steel.
[0051] In this case, the amount of raw material powder filled into the stainless steel mill container is preferably such that the mass ratio of raw material powder to balls is 1 / 100 to 1 / 3. If the mass ratio of raw material powder to balls exceeds 1 / 100, the amount of impurities mixed in is reduced, and if the mass ratio of raw material powder to balls is below 1 / 3, an alloy coating layer with finer Al-containing phase and Zn-containing phase can be obtained.
[0052] When it is desired to suppress the inclusion of impurities, it is preferable to perform milling in an inert gas atmosphere such as N2 or Ar or a vacuum atmosphere inside the mill container.
[0053] In this embodiment, the conditions of ball milling for performing mechanical alloying are not limited, but in order to obtain an alloy coating layer in which the Al-containing phase and the Zn-containing phase are finer, it is preferable that the revolution speed in the planetary ball mill method is 400 to 1000 rpm, the rotation speed is 800 to 2000 rpm, and the treatment time is 5 hours or more. The treatment time may be 10 hours or more. In addition, the treatment time may be 36 hours or less, 24 hours or less, 20 hours or less, or 18 hours or less.
[0054] It is preferable to fill a container with 0.1 to 3% by mass of ethanol relative to the amount of the raw material powder, together with the raw material powder and balls, and then perform milling, as this can prevent the raw material powder from adhering to the inner wall of the container and improve the yield of alloy powder.
[0055] The raw powder pulverized and mechanically alloyed by the ball mill needs to be compression molded on a steel plate before sintering. The alloy coating layer of this embodiment does not limit the method of compression molding, but it is preferable to perform the work in an inert gas atmosphere such as N2 or Ar until the powder is taken out of the mill container and compression molded. This is to prevent air containing oxygen from being trapped between the powder in the compression molded body when the raw powder after milling is compression molded, which causes oxidation inside the sintered body in the sintering process.
[0056] In this embodiment, the sintering method is not limited, but if it is desired to produce a dense sintered body with fewer voids in a shorter time, it is preferable to use the spark plasma sintering method. The spark plasma sintering method is also called the pulse current method, the pulse current pressure sintering method, the plasma activation sintering method, the current heating sintering method, etc., and is a method in which powder or solids are filled into a graphite sintering mold and heated by pulse current while applying pressure. Since the compression-molded powder is heated by directly passing an electric current through it, it has the advantage that sintering is completed at a low temperature and in a short time, and there are fewer voids in the produced sintered body, compared to other powder metallurgy methods such as the hot press method.
[0057] In this embodiment, the heating temperature and heating time during sintering are not limited. However, when the alloy coating layer is produced by spark plasma sintering, the maximum heating temperature during spark plasma sintering is set to T max (℃), and the melting point of the Al-Zn alloy estimated from the Al-Zn binary phase diagram is T mp (℃), T mp ×0.6 <T max <T mp Sintering under the condition of 0.95× is preferable because it allows the production of a sintered body with fewer voids in a shorter time. Note that the temperature specified here is not the temperature of the plasma formed by the discharge occurring between particles during sintering, but the temperature measured by a thermocouple embedded in a graphite sintering mold. This temperature means the temperature set at a distance of 5 mm to 10 mm between the temperature measuring part of the thermocouple and the compression molded body to be sintered.
[0058] In this manner, the Al-Zn-based alloy coated steel sheet of the present embodiment can be manufactured. EXAMPLES
[0059] Examples will now be described. The steel sheets were cut out to a size of 180 mm x 100 mm from a cold-rolled steel sheet with a thickness of 0.8 mm. Both were SS400 (general steel). The raw materials used were Zn powder (purity 99.99%) and Al powder (purity 99.9%). The Zn powders were prepared with particle sizes of 75 μm or less, 84 μm or less, 86 μm or less, 89 μm or less, and 180 μm or less. The Al powders were prepared with particle sizes of 300 μm or less, 850 μm or less, 180 μm or less, 150 μm or less, and 30 μm or less. The mixed powders were prepared so that the Al and Zn amounts after mixing the Al and Zn powders were as shown in Tables 1 and 2. In Tables 1 and 2, the impurity amounts were less than 0.1%.
[0060] The raw powder, 1% ethanol (mass %) based on the amount of the raw powder, and stainless steel balls were loaded into a stainless steel milling vessel, and ball milling was performed in an Ar gas atmosphere inside the milling vessel. The mass ratio of raw powder to balls was 1 / 5. The revolution speed in the planetary ball milling method was 500 rpm, the rotation speed was 1000 rpm, and the treatment time was 1 to 36 hours. The balls were stainless steel balls with a diameter of 15 mm.
[0061] Next, before sintering, a steel plate was placed inside a graphite sintering mold in an Ar gas atmosphere, and the mixed powder was placed on one side and the other side of the steel plate. The mixed powder was then compression molded with a pressure of 1 kN. The amount of raw material powder on both sides of the steel plate was such that the amount of the alloy coating layer attached was 75 g / m on each side. 2 It was adjusted to be.
[0062] The sintering method used was the spark plasma sintering method. Using a graphite sintering mold containing the raw material powder and steel plate after compression molding, the spark plasma sintering method was carried out by pulse current in an Ar gas atmosphere. The heating temperature was 400°C and the heating time was 5 minutes. The heating temperature was T mp ×0.6 <T max <T mp The condition of ×0.95 was met.
[0063] In this manner, Al-Zn alloy-coated steel sheets having alloy coating layers shown in Tables 3 and 4 on both sides of the steel sheets were produced.
[0064] For the obtained Al-Zn alloy coated steel sheets, the average KAM value of the Zn-containing phase and the Al-containing phase in the alloy coating layer, the half-width of the X-ray diffraction peak of the (203) plane of Zn, the half-width of the X-ray diffraction peak of the (331) plane of Al, and the average grain size of the Zn-containing phase and the Al-containing phase, where the region surrounded by grain boundaries with an average crystal orientation difference of 15° or more is defined as a crystal grain by EBSD analysis, were measured. The respective measurement methods and measurement conditions were as follows.
[0065] (Chemical composition of Zn-containing phase and Al-containing phase) The elements constituting the Zn-containing phase and the Al-containing phase were quantitatively analyzed by an energy dispersive X-ray spectroscopy (EDS) attached to a transmission electron microscope (TEM). Specifically, a test piece was cut out from an Al-Zn alloy-coated steel plate on which an alloy coating layer was formed by a cryo-FIB (Focused Ion Beam) method, and the cross-sectional structure of the cut out test piece was observed by a TEM at a magnification where multiple pieces of each phase were included in the observation field. The transmission electron microscope used was JEM-2100F (manufactured by JEOL Ltd.), the EDS measurement device used was JED-2300T (manufactured by JEOL Ltd.), and the FIB device used was NB5000 (manufactured by Hitachi High-Technologies Corporation). The cutting out by the FIB method was performed at an acceleration voltage of 40 to 5 kV after forming an Au vapor deposition film as an electron irradiation protection film before TEM observation. A Cu mesh was used as the sample holding mesh. To identify the constituent elements of each phase, quantitative analysis of Zn and Al was performed at five or more points in each phase using TEM-EDS. The average values of the Zn and Al concentrations at each point in each phase were adopted as the chemical composition of each phase. Observation and EDS analysis were performed at an accelerating voltage of 200 kV and a probe diameter of 1 nmΦ. In this way, it was confirmed that the alloy coating layer contained Zn-containing phases and Al-containing phases.
[0066] (KAM value and average particle size) A test piece was cut out from the steel plate on which the alloy coating layer was formed by the cryo-FIB (Focused Ion Beam) method. Then, the surface of the alloy coating layer was polished using #1500 silicon carbide paper, and then it was finished to a mirror surface using a liquid in which diamond powder with a particle size of 1 to 6 μm was dispersed in a lubricating liquid containing alcohol, and further a final polishing was performed using colloidal silica. In this way, the measurement sample was prepared.
[0067] The measurement samples were observed using a scanning electron microscope. The scanning electron microscope used was equipped with an EBSD analysis device and an EDS measurement device. The scanning electron microscope used was a Hitachi High-Technologies Corporation-manufactured scanning electron microscope (FE-SEM: SU-70), the EBSD analysis device was a Digi View (TSL Solutions), and the EDS measurement device was an Octan elect super (Ametech).
[0068] The measurement magnification was 5000 times, the measurement area was a 15 μm × 30 μm area of the coating layer cross section, the measurement interval was 0.03 μm step, the acceleration voltage was 15 kV, and the working distance was 15 mm, and the secondary electron image was taken with a scanning electron microscope.
[0069] The obtained images were subjected to elemental analysis by EDS to identify the Zn-containing phase and the Al-containing phase. The Zn-containing phase was defined as the region where 80 atomic % or more of Zn was detected, and the Al-containing phase was defined as the region where 80 atomic % or more of Al was detected.
[0070] Next, the same field of view was subjected to EBSD analysis at an analysis speed of 200 to 300 points / second using an EBSD analyzer. The average grain size of the Al-containing phase and the Zn-containing phase was calculated using the software "OIM Analysis (registered trademark)" attached to the EBSD analyzer. For the crystal orientation information obtained by EBSD analysis, the region surrounded by grain boundaries with an average crystal orientation difference of 15° or more was defined as a crystal grain, and the average crystal grain size was calculated. In calculating the average crystal grain size, the measurement target was crystal grains with a grain size of 0.05 μm or more.
[0071] Next, the KAM value was measured under the following conditions using the software "OIM Analysis (registered trademark)".
[0072] Nearest neighbor: 1st (If it is 1st, the azimuth difference is calculated using the nearest pixel.) Perimeter only If there is a difference in direction of 5° or more, all directions are specified as a difference of 5°. ·Maximum orientation difference: within 5°
[0073] (X-ray diffraction peak half-width) As a sample pretreatment, the measurement sample used for EBSD analysis was chemically polished to a depth of about 3 μm with a mixture of diluted hydrofluoric acid and nitric acid to remove polishing distortion. Then, X-ray diffraction measurements were performed under the conditions shown in Table 2, and the X-ray diffraction peaks of the Zn (203) plane and the Al (331) plane were identified. The diffraction peak position 2θ and half-width WL were obtained by fitting with a Lorentzian function after removing the background and Kα2 radiation. The half-width derived from the instrument was obtained by interpolation using the half-width of the standard sample (LaB6). The true half-width was obtained by subtracting the "half-width derived from the instrument" from the "half-width of the sample".
[0074] [Table 2]
[0075] The average chemical composition of the alloy coating layer was determined by preparing an acid solution by peeling and dissolving the alloy coating layer with an acid containing an inhibitor that suppresses corrosion of the steel plate, and then measuring the acid solution using ICP atomic emission spectrometry and ICP-MS.
[0076] (Corrosion resistance on flat surfaces) The flat surface corrosion resistance was evaluated as follows. The obtained Al-Zn alloy coated steel sheets were cut into 100mm x 50mm pieces and subjected to a salt spray test conforming to JIS Z 2371:2015 for up to 500 hours. The flat surface corrosion resistance was evaluated based on the corrosion weight loss of the test pieces after the test. The evaluation criteria for flat surface corrosion resistance are as follows. "S", "AA" and "A" were considered to be passing grades.
[0077] S: Corrosion loss is 0.020 (g / m 2 / hr) or less AA: Corrosion weight loss is over 0.020 to 0.028 (g / m 2 / hr) or less A: Corrosion weight loss is over 0.028 to 0.10 (g / m 2 / hr) or less B: Corrosion loss is greater than 0.10 to 0.50 (g / m 2 / hr) or less C: Corrosion loss is 0.50 (g / m 2 / hr) super
[0078] (Corrosion resistance of end face) The corrosion resistance of the edge surface was evaluated as follows. The obtained Al-Zn alloy coated steel plate was cut to 100 mm x 50 mm, and the top and bottom ends (50 mm sides) were sealed with 10 mm of polyester tape, after which a salt spray test conforming to JIS Z 2371 (2015) was carried out for up to 8,400 hours, and the corrosion resistance of the edge surface was evaluated based on the average distance (mm) from the cut edge surface (100 mm side) of the test piece where red rust had developed after the test. After the corrosion test, the exterior was photographed using a digital camera, and the area of red rust development (S, mm 2 ) was obtained. The average distance where red rust occurred was calculated by dividing the area where red rust occurred by the distance of 80 mm from the cut end surface (see Fig. 2. The units of values in Fig. 2 are mm). The evaluation criteria for edge corrosion resistance are as follows. "S", "AA" and "A" were considered to be passing.
[0079] S: 10mm or less AA: More than 10~12mm or less A: More than 12~14mm or less B: More than 14~18mm or less C: More than 18mm
[0080] [Table 3]
[0081] [Table 4]
[0082] In Examples 1-1 to 1-8 of the present invention, a Zn-containing phase and an Al-containing phase were contained in the alloy coating layer, and the average KAM value and average grain size of each were as shown in Table 3, and the corrosion resistance of the flat surface and the end surface were excellent.
[0083] On the other hand, in Comparative Examples 2-1 to 2-10, the alloy coating layer contained a Zn-containing phase and an Al-containing phase, but the average KAM value and average grain size of each were as shown in Table 4. Since the average KAM value of one or both of the Zn-containing phase and the Al-containing phase was outside the range of the present invention, both the flat surface corrosion resistance and the end surface corrosion resistance were deteriorated.
[0084] In Comparative Example 2-1, the particle size range of the raw material Al powder exceeded 180 μm, and the average KAM values of both the Zn-containing phase and the Al-containing phase were outside the range of the present invention.
[0085] In Comparative Example 2-2, the grain size range of the Al powder, which is the raw material powder, exceeds 180 μm, and the grain size range of the Zn powder exceeds 75 μm, so that the average KAM value of the Zn-containing phase was outside the range of the present invention.
[0086] In Comparative Examples 2-3 and 2-4, the particle size range of the Zn powder as the raw material powder exceeded 75 μm, and the average KAM values of both the Zn-containing phase and the Al-containing phase were outside the range of the present invention.
[0087] In Comparative Examples 2-5, 2-6, and 2-7, the ball milling treatment time was less than 5 hours, so that the average KAM value of one or both of the Zn-containing phase and the Al-containing phase was outside the range of the present invention.
[0088] In Comparative Example 2-8, the particle size range of the raw material powder Al powder exceeded 180 μm and the particle size range of the raw material powder Zn powder exceeded 75 μm. Furthermore, the ball milling processing time was less than 5 hours, so the average KAM value of the Zn-containing phase was outside the range of the present invention.
[0089] In Comparative Example 2-9, the Al concentration was less than 6%, so that the average KAM values of both the Zn-containing phase and the Al-containing phase were outside the range of the present invention.
[0090] In Comparative Example 2-10, the Al concentration exceeded 80%, so that the average KAM values of both the Zn-containing phase and the Al-containing phase were outside the range of the present invention.
Claims
1. A steel plate and an alloy coating layer containing Zn and Al arranged on a surface of the steel plate, The average chemical composition of the alloy coating layer contains 6 to 80 mass% Al, with the remainder being Zn and impurities, The metal structure of the alloy coating layer is composed of a phase containing 80 atomic % or more of Zn and a phase containing 80 atomic % or more of Al, The phase containing 80 atomic % or more of Zn has a KAM value of 0.55 to 0.70°, and the phase containing 80 atomic % or more of Al has a KAM value of 1.00 to 4.00°.
2. The X-ray diffraction peak half width of the (203) plane of the phase containing 80 atomic % or more of Zn is in the range of 0.18 to 0.24°, 2. The Al-Zn alloy coated steel sheet according to claim 1, wherein the half width of the X-ray diffraction peak of the (331) plane of the phase containing 80 atomic % or more of Al is in the range of 0.34 to 0.60°.
3. The Al-Zn based alloy coated steel sheet according to claim 1 or claim 2, wherein, when a region surrounded by a grain boundary having an average crystal orientation difference of 15° or more by EBSD analysis is defined as a crystal grain, the average grain size of the phase containing 80 atomic % or more of Zn is in the range of 0.1 to 4 μm, and the average grain size of the phase containing 80 atomic % or more of Al is in the range of 0.1 to 4 μm.
Citation Information
Patent Citations
Manufacture of corrosion resistance zinc alloy coated steel wire
JP1989180909A
Mg-containing zn-alloy-coated steel material
WO2017057638A1